2017
DOI: 10.1016/j.imbio.2017.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-specific nanotechnology-driven CD163 overexpression in human macrophages results in an M2 phenotype under inflammatory conditions

Abstract: M1 macrophages release pro-inflammatory factors during inflammation. They transition to an M2 phenotype and release anti-inflammatory factors to resolve inflammation. An imbalance in the transition from M1 to M2 phenotype in macrophages contributes to the development of persistent inflammation. CD163, a member of the scavenger receptor cysteine-rich family, is an M2 macrophage marker. The functional role of CD163 during the resolution of inflammation is not completely known. We postulate that CD163 contributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 60 publications
(83 reference statements)
1
60
0
2
Order By: Relevance
“…Macrophages participate in this process by maintaining the in ammatory and brogenic environment (41). CD163 promotes the transformation of macrophages from M1 to M2 phenotype and releases antiin ammatory factors to solve in ammation (42). In our analysis, CD163 was down regulated in HCM, which may be a key factor in the persistent in ammatory environment of HCM.…”
Section: Discussionmentioning
confidence: 57%
“…Macrophages participate in this process by maintaining the in ammatory and brogenic environment (41). CD163 promotes the transformation of macrophages from M1 to M2 phenotype and releases antiin ammatory factors to solve in ammation (42). In our analysis, CD163 was down regulated in HCM, which may be a key factor in the persistent in ammatory environment of HCM.…”
Section: Discussionmentioning
confidence: 57%
“…The present results establish that a tolerogenic vaccine able to mitigate EAE in inbred SPF mice through MOG-targeting to peripheral DC and induction of FOXP3+ suppressor Tregs (Idoyaga et al , 2013; Ring et al , 2013) also applies to outbred adult primates with a trained immune system. In mice, tolerogenic priming relied on the ability of particular DC subsets to produce TGF β (Idoyaga et al , 2013; Ring et al , 2013; Yamazaki et al , 2008), a cytokine also produced by CD163+ M2 macrophages (Zaba et al , 2007; Alvarado-Vazquez et al , 2017). These CD163+ macaque’s skin macrophage have migratory properties as they are also retrieved in lymph nodes (Adam et al , 2015).…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Interestingly, CD163overexpressing macrophages inhibit LPS-induced inflammation in vitro. 25 Furuhashi et al. also found that CD163-expressing macrophages are associated with IL-10 production as an anti-inflammatory cytokine in anti-GBM glomerulonephritis rat.…”
Section: Introductionmentioning
confidence: 95%